PENGARUH SELF-COMPASSION TERHADAP KESEPIAN PADA MAHASISWA RANTAU - Pratiwi, Diani; Dahlan, Tina Hayati; Damaianti, Lira Fessia (JURNAL PSIKOLOGI INSIGHT, 2019)
This study aimed to determine the effect of self-compassion on loneliness, of overseas student in University of Education Indonesia. The study used quantitative method with 260 participants. The research used instruments Indonesian Self-compassion Scale – Short Version (Oktyana, 2013) and UCLA Loneliness Scale Version 3 to measure loneliness adapted by Irsalina (2013) from Rusell (1996). This used simple regression to analyze the effect of Self Compassion to Lonelines. The result showed there were significant effect of self-compassion to loneliness with R square 0,096. The freshmen tend to lonelines, so the university must overcome their loneliness.